2023
DOI: 10.3389/fnut.2023.1143682
|View full text |Cite
|
Sign up to set email alerts
|

β-glucans: a potential source for maintaining gut microbiota and the immune system

Abstract: The human gastrointestinal (GI) tract holds a complex and dynamic population of microbial communities, which exerts a marked influence on the host physiology during homeostasis and disease conditions. Diet is considered one of the main factors in structuring the gut microbiota across a lifespan. Intestinal microbial communities play a vital role in sustaining immune and metabolic homeostasis as well as protecting against pathogens. The negatively altered gut bacterial composition has related to many inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 277 publications
0
11
0
Order By: Relevance
“…Additionally, BG‐C and BG‐S exhibited approximately four‐time greater resistance to digestion compared to inulin. Singh & Bhardwaj (2023) similarly reported on the ability of ß‐glucan to resist digestion and absorption in both the gastric and small intestine. Our study confirmed that BG‐C and BG‐S could resist digestion in simulated gastric conditions by 94.71% and 99.07%, respectively, and in the small intestine by 91.63% and 99.43%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, BG‐C and BG‐S exhibited approximately four‐time greater resistance to digestion compared to inulin. Singh & Bhardwaj (2023) similarly reported on the ability of ß‐glucan to resist digestion and absorption in both the gastric and small intestine. Our study confirmed that BG‐C and BG‐S could resist digestion in simulated gastric conditions by 94.71% and 99.07%, respectively, and in the small intestine by 91.63% and 99.43%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…GRS contains Polyporus sclerotium and Poria sclerotium, which are rich sources of β‐glucans [31, 32]. β‐Glucans have been reported to alter the gut microbiota [33, 34], suggesting that they may play a role in the modification of gut microbiota composition and the increased formation of secondary bile acids. Therefore, the estimations of the content of β‐glucans and their chemical and biological characterizations are necessary to elucidate the modulation of gut microbiota by GRS.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noticed that, in the three EPS samples, the amount of glucose is extremely high in comparison to that of all of the other monomers. The possible explanation could be that there might be glucose-rich glycans, such as β glucan or lipopolysaccharides produced as part of the EPS . Further investigation is needed to understand the high glucose content.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation could be that there might be glucose-rich glycans, such as β glucan or lipopolysaccharides produced as part of the EPS. 29 Further investigation is needed to understand the high glucose content.…”
Section: Discussionmentioning
confidence: 99%